POTENSI KOMODITAS PANGAN SUMBER KARBOHIDRAT DALAM MENDUKUNG KETAHANAN PANGAN DI KECAMATAN SUMBANG KABUPATEN BANYUMAS - Widayaningsih, Neni; , Sukarsih; Setiasih, Endang; , Barokatuminalloh (Prosiding, 2012)
The background of this research is the phenomenon of the still low condition of food security at the household level in Sumbang District Banyumas Regency. The general objective of this study was to identify the areas and food commodities that support food security, while the specific objectives were to identify: food security by focusing on the availability of carbohydrates based foods; the food commodities which is the basic food commodities, the food commodities which are growth dominant food commodities in Sumbang District Banyumas Regency which is potential to be developed. This research has a very important meaning because it generates information about the state of food security, basic food commodities and growth dominant food commodities that are feasible to develop. The approach used was multidisciplinary science between agricultural economics and regional economics. The research method used was qualitative and quantitative methods. The reesearch sites was in Sumbang District Banyumas Regency that covers 19 regions of village. Data mining technique was done by observation, structured interviews, while the informant determination technique using snowball techniques. The analysis of the data was done by the analysis of Food Security, Location Quotient (LQ), Growth Ratio Model (MRP), and Overlay. The results showed that food security seen from the availability of carbohydrates foods in the District of Sumbang is still very low, as seen from the average number of food security from 2005 to 2010 that is still far from 1. Figures for watered field rice food supply is by an average of 0.148 and not watered field rice by an average of 0.004. While the availability of food for corn is by an average of 0.036, and for cassava is an average of 0.0062. Carbohydrates based food commodities which is the basic food commodities which have an average value of LQ greater than one from 2005 to 2010 is cassava, but it showed a negative trend (decline). Then the food commodities of watered field rice and corn showed a positive trend values (increasing), although both average value of LQ are less than one. While the not watered rice food commodities which had the average value of LQ less than one, also showed a negative trend (declining). The watered field rice show the value of RPs (+), meaning that the food commodities in the district of Sumbang has a rapid growth. This food commodities is expected to has a great role in contributing to the growth in the region of both Sumbang District and also Banyumas Regency. Thus it can be said that the district of Sumbang has the advantage in the development of watered field rice food commodities, though the commodity has an average LQ value less than one, but have a positive trend (increasing) and also has a rapid growth. Therefore, these food commodities are potentially viable commodities to be developed in the region to support food security. Strategy or policy that can be done by Dinas Pertanian dan Tanaman Pangan to increase agricultural production is by increasing farmers understanding in terms of the 2 maximum crop production and according to the characteristics of the area and the land, also knowledge about sustainable agriculture, it should be done so the optimal results obtained at the time can also be reproduced for the periods to come so that the food availability is always sustained. Furthermore, that also needs to be improved is the peoples understanding about food, so that people do not always depend on just one source of carbohydrates, especially rice, but there are other sources of carbohydrates such as corn and cassava, given corn food commodities also showed a positive trend (increasing), so people should not experience anxiety when there is a shortage of rice. Factor that also not less important in terms of food is to improve education or knowledge about nutrition such as an understanding that the food needed by the body is not just carbs but it also requires other source of nutrients such as protein and other micro nutrients. For that reason one of government program (Ministry of Agriculture Food Security Agency) is the fortification which should be done with careful calculation, so that goal of adequate nutrition for community is achieved.